A causality between fruit consumption and colorectal cancer: a two-sample Mendelian randomization analysis - Yang, Li (Frontiers in Oncology, 2024)
Background Colorectal cancer (CRC) significantly threatens human health with increasing incidence and mortality. A debate continues whether fruit consumption is associated with CRC, despite dietary habits having an impact on the disease. The study aims to examine the causal relationship between fruit consumption and CRC based on a two-sample Mendelian randomization method (MR). Methods Summary statistics for fruit consumption and CRC were obtained from the UK Biobank and the FinnGen Consortium, respectively. Analysis methods used in this study included the inverse-variance weighted (IVW), MR Egger, weighted median, simple mode, and weighted mode. Heterogeneity and horizontal pleiotropy were also assessed. Additionally, a leave-one-out analysis was performed to validate the robustness of the results. Results We found that fruit consumption was associated with a reduction in CRC risk by the IVW method (P = 0.021). This protective effect was predominantly observed in males (OR 0.374; 95% CI: 0.157-0.892; P = 0.027), while no protective effect was noted in females. However, causal correlations were not observed upon analyzing 16 individual types of fruits. Moreover, our results were unlikely to be influenced by horizontal pleiotropy and heterogeneity. Leave-one-out analysis confirmed the stability of the results. Conclusion Our findings suggest that a genetic predisposition for fruit consumption may be protective against CRC, underscoring the need for further research to elucidate the underlying mechanisms and dietary patterns involved.